High‐Temperature Viscoelastic Relaxation in All‐Cellulose Composites. Issue 1 (June 2014) - Duchemin, Benoît J.C.; Staiger, Mark P.; Newman, Roger H.; Saiter, Jean‐Marc
Summary All‐cellulose composites were prepared across a range of different crystallinities in order to examine relationships between phase composition and viscoelastic behaviour in the temperature range of 270 °C to 340 °C corresponding to the α1 mechanical relaxation. Composite films were prepared by partial dissolution of microcrystalline cellulose in a LiCl/N, N‐dimethylacetamide (LiCl/DMAc) solvent system using the film casting technique. Dynamic mechanical analysis showed two contributions to α1 relaxation, with tan δ maxima at 303 ± 2 °C and at approximately 325 °C. The height of the maximum or shoulder at 303 ± 2 °C decreased with increasing crystallinity, and was therefore assigned to molecular motion associated with chemical decomposition in non‐crystalline domains. The maximum at 325 °C was assigned to chemical decomposition in chains associated with the surfaces of crystalline domains. Composites with high crystallinity showed best retention of the dynamic storage modulus when tested at 300 °C.